Diffuse Myocardial Fibrosis Reduces Electrocardiographic Voltage Measures of Left Ventricular Hypertrophy Independent of Left Ventricular Mass. Issue 1 (22nd January 2017) - Maanja, Maren; Wieslander, Björn; Schlegel, Todd T.; Bacharova, Ljuba; Abu Daya, Hussein; Fridman, Yaron; Wong, Timothy C.; Schelbert, Erik B.; Ugander, Martin
Abstract : Background: Myocardial fibrosis quantified by myocardial extracellular volume fraction (ECV) and left ventricular mass (LVM) index (LVMI) measured by cardiovascular magnetic resonance might represent independent and opposing contributors to ECG voltage measures of left ventricular hypertrophy (LVH). Diffuse myocardial fibrosis can occur in LVH and interfere with ECG voltage measures. This phenomenon could explain the decreased sensitivity of LVH detectable by ECG, a fundamental diagnostic tool in cardiology. Methods and Results: We identified 77 patients (median age, 53 [interquartile range, 26–60] years; 49% female) referred for contrast‐enhanced cardiovascular magnetic resonance with ECV measures and 12‐lead ECG. Exclusion criteria included clinical confounders that might influence ECG measures of LVH. We evaluated ECG voltage‐based LVH measures, including Sokolow‐Lyon index, Cornell voltage, 12‐lead voltage, and the vectorcardiogram spatial QRS voltage, with respect to LVMI and ECV. ECV and LVMI were not correlated ( R 2 =0.02; P =0.25). For all voltage‐related parameters, higher LVMI resulted in greater voltage ( r =0.33–0.49; P <0.05 for all), whereas increased ECV resulted in lower voltage ( r =−0.32 to −0.57; P <0.05 for all). When accounting for body fat, LV end‐diastolic volume, and mass‐to‐volume ratio, both LVMI (β=0.58, P =0.03) and ECV (β=−0.46, P <0.001) were independent predictors of QRS voltage (multivariate adjusted R 2 =0.39; P <0.001). Conclusions: Myocardial mass and diffuse myocardial fibrosis have independent and opposing effects upon ECG voltage measures of LVH. Diffuse myocardial fibrosis quantified by ECV can obscure the ECG manifestations of increased LVM. This provides mechanistic insight, which can explain the limited sensitivity of the ECG for detecting increased LVM.